Husband-Wife income sharing from al-Ma'ruf perspective / Azhar Abdul Aziz … [et al.] - Abdul Aziz, Azhar; Ab. Manan, Siti Khadijah; Alias, Baterah; Muhamad, Wan Ismail (Academy of Contemporary Islamic Studies, 2015)
Current scenario has indicated that the number of women going to work is increasing and cases of wives having more incomes than their husbands are common. This has led to a question of whose responsibility is the expenditure of a family, particularly when the husbands are having lesser incomes. The concept of income sharing between husband and wife is seen as a solution to the issue. This study attempted to examine the al-ma 'ruf concept of income sharing from the view of the scholars. The survey method was then adopted to examine the current practice of income sharing under the al-ma 'ruf concept. Finding of the study showed that a significant number of husbands neglect their responsibilities to bear the financial rights of the wives, thus non-complying the ma'ruf concept. The study proposed for the husbands to strive harder in fulfilling their responsibilities to finance the expenditure of the family.